EXPRESSÃO ISOENZIMÁTICA DE LINHAGES ENDOGÂMICAS S1 DE MILHO - Schneider, Ricardo De Oliveira; Sangiovo, Jaqueline Piesanti; Morizzo, Leomir; Bubans, Valéria Escaio; Carvalho, Ivan Ricardo (Salão do Conhecimento, 2019)
projeto de pesquisa realizado no curso de agronomia da unijuí